PERANCANGAN BUKU KOMIK BAHAYA NARKOBA TERHADAP ANAK - Jusep Kurnia; m.nasrul kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Drug abuse has an adverse effect which can lead to addiction (addiction) which results in  dependency. Drug abuse in Indonesia is increasingly happening in some circles ranging from people with low and high economics.The purpose of designing this comic is to inform children about the dangers of drugs and as a precautionary measure so as not to increase drug abuse. The chosen media is comic books because comic books have a lot of pictures so it is interesting for children.This design produced a comic book as the main media, and was also supported by several other media, namely: Poster, Sticker, Totebag, X-banner, Tshirt, Key Chain, and Backdrop as supporting the main media and as a promotional media.Keywords: Comics, Drugs.